Crohn's disease: Aspects of interest to the surgeon - Castelli, Fernando; Maglione, Oscar; Canessa, César; Perrier, José Pedro; Varela, Daniel (Cirugía del Uruguay, 2004)
Crohn 's di sea se is basical/y a pathology requiring medica/ treatment; however in 60% of cases it has need of surgica/ procedures, be it to due to failure of the ormer or for the manner in which it presents itself or due to the presence of complications. Consequently acquaintance with this pathology by surgeons is important, either due to its pathogenic aspects or because the therapy approach is conditioned by the anatomo-pathologic form adopted or by its complications. The paper contains an analysis of clínica/ cases treated by the authors with various forms of presentation, study and treatment